2022
DOI: 10.1021/acs.est.2c04240
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Ecosystem Function from Dissolved Organic Matter Optical Properties: A Critical Review

Abstract: Over the last 30 years, the optical property community has shifted from conducting dissolved organic matter (DOM) measurements on new complex mixtures in natural and engineered systems to furthering ecosystem understanding in the context of past, present, and future carbon (C) cycling regimes. However, the appropriate use of optical properties to understand DOM behavior in complex biogeochemical systems is of recent debate. This critical review provides an extensive survey of DOM optical property literature ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 164 publications
1
36
0
Order By: Relevance
“…This is apparent from simple spectroscopy measurements (Fig. 1) (D'Andrilli et al 2022) but is also evident from the suite of new analytical techniques such as high-resolution mass spectrometry, electrochemical redox characterizations, and improved functional group analysis (McAdams et al 2018;McKnight et al 2001;D'Andrilli et al 2013D'Andrilli et al , 2022Cawley et al 2013). A dendritic representation of NOM is more appropriate Fig.…”
Section: Need For Unique End-member Sitesmentioning
confidence: 99%
“…This is apparent from simple spectroscopy measurements (Fig. 1) (D'Andrilli et al 2022) but is also evident from the suite of new analytical techniques such as high-resolution mass spectrometry, electrochemical redox characterizations, and improved functional group analysis (McAdams et al 2018;McKnight et al 2001;D'Andrilli et al 2013D'Andrilli et al , 2022Cawley et al 2013). A dendritic representation of NOM is more appropriate Fig.…”
Section: Need For Unique End-member Sitesmentioning
confidence: 99%
“…Previous studies showed that the optical parameters could provide valuable information on the source and composition of DOM in aquatic environments (Baker, 2001;Chen et al, 2010;Derrien et al, 2017;Li and Hur, 2017;D'Andrilli et al, 2022). The relatively high contribution of humic-like components to total FDOM fluorescence was found in both the groundwater (77 ± 18%) and river water samples (88 ± 7%), suggesting that the highly reworked humic-like molecules dominate the riverine and groundwater DOM pool (Figure 5A).…”
Section: Factors Affecting the Sources Compositions And Levels Of Dom...mentioning
confidence: 82%
“…As shown in Figure b, n A values had a good linear correlation with SUVA 254 values, suggesting that other parameters may be also used for the modeling purpose to group DOM molecules. It is desired to elucidate the origins of these molecular groups and quantify them in a simple and direct way with mechanistic insights, for example, approaches combined with optical properties of DOM or with advanced computation methods (e.g., machine learning method). , Since both climate and soil properties significantly affect the compositions and properties of soil DOM, , we hope our results will help to predict the chemodiversity and reactivity of DOM in the soil environment by incorporating both the (bio)­geochemical processes and molecular-level insight into soil DOM models.…”
Section: Resultsmentioning
confidence: 99%